Dinosaur train. Adventure Island [videorecording (DVD)] - Bartlett, Craig (PBS Distribution, 2020)
The Pteranodon family takes the Dinosaur Train to Adventure Island, a new theme park on a volcanic island. The Conductor's archrival Thurston is in charge: he proudly shows off the park's amazing robot dinosaurs.